2018
DOI: 10.1186/s13005-018-0176-2
|View full text |Cite
|
Sign up to set email alerts
|

Quality of occlusal outcome following space closure in cases of lower second premolar aplasia using lingual orthodontic molar mesialization without maxillary counterbalancing extraction

Abstract: BackgroundControlled space closure in cases of isolated lower second premolar aplasia (ILSPA) without maxillary counterbalancing extraction is challenging. Anterior anchorage loss may occur during space closure resulting in compromised occlusal results in terms of an absence of proper canine guidance during laterotrusive mandible movements.In order to evaluate the effectiveness of Herbst telescope anchorage in combination with double-cable, pull mechanics and a completely customized lingual appliance for ortho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
(45 reference statements)
0
6
0
1
Order By: Relevance
“…The integral indicator of the quality of treatment must take into account the timing of rehabilitation, since the use of the mini-implants as a promising method of orthodontic correction, can reduce the total time needed for iatrogenic interventions [5][6][7]. On the other hand, the terms of treatment, together with the parameters of functional and aesthetic restorations, affect the patient's satisfaction criterion due to the chosen appropriate rehabilitation algorithm.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The integral indicator of the quality of treatment must take into account the timing of rehabilitation, since the use of the mini-implants as a promising method of orthodontic correction, can reduce the total time needed for iatrogenic interventions [5][6][7]. On the other hand, the terms of treatment, together with the parameters of functional and aesthetic restorations, affect the patient's satisfaction criterion due to the chosen appropriate rehabilitation algorithm.…”
Section: Discussionmentioning
confidence: 99%
“…Realization of such procedures without using any additional anchorage outlined by possible non-prognostic undesired effects. Previous results obtained during in vivo and in vitro studies suggested that after tooth movement in the form of mesialization there is a chance of periodontal support loss, but except that adverse effect of mesialization procedure could be associated with the rotation of mesialized tooth, its extrusion and non-preferable changes in occlusal force distribution [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…An edge-to-edge position of the respective mesial and distal sides of upper and lower first premolar was defined as a sagittal distal occlusion of ½ cusp. The true dimensions of the assessed premolar and malocclusion on the digital photographs were assessed using a calibration technique previously employed [13]: The intraoral photographs were scaled to the corresponding plaster casts by adjusting the dimensions of the upper first premolar to its corresponding dimensions taken from direct cast measurements, using a sliding caliper. In cases in which there were different extents of sagittal occlusion on either side, the side with greater Angle class II occlusion was chosen for assessment.…”
Section: Assessment Of Occlusion and Spacingmentioning
confidence: 99%